SOME FEATURES OF THE RIGHT OF OWNERSHIP TO NATURAL RESOURCES IN THE RA LEGISLATION AND PRACTICE - Geghamyan, Olympia (State and Law, 2020)
The present article is devoted to the right of ownership to natural resources that is primary importance to any country as well as to the Republic of Armenia. The article outlines the legislative regulations, tha gaps, shortcomes and practice.The article presents constitutional regulations in different periods and current sectoral regulatons.As a result of that analisys, several proposals are introduced which, in our opinion, will contribute to the improvement of legislation and the effective realization of the right of ownership to natural resources.
Keywords: the right of ownership to natural resources, the object of the right of ownership to natural resources, forms of the right of ownership to natural resources